2010
DOI: 10.1021/nl9041966
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Transport in Suspended and Supported Monolayer Graphene Grown by Chemical Vapor Deposition

Abstract: Graphene monolayer has been grown by chemical vapor deposition on copper and then suspended over a hole. By measuring the laser heating and monitoring the Raman G peak, we obtain room-temperature thermal conductivity and interface conductance of (370 + 650/-320) W/m K and (28 + 16/-9.2) MW/m(2) K for the supported graphene. The thermal conductivity of the suspended graphene exceeds (2500 + 1100/-1050) W/m K near 350 K and becomes (1400 + 500/-480) W/m K at about 500 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

66
1,032
8
9

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,147 publications
(1,115 citation statements)
references
References 34 publications
66
1,032
8
9
Order By: Relevance
“…2500 W · m − 1 · K − 1 ). [ 9 ] These results indicate that the crystallinity of the 2D sheets affects signifi cantly the thermal properties. Therefore, if one is to exploit the outstanding thermal properties of graphene, it is important to synthesize extremely high crystalline graphene so that the fabrication of heat dissipaters and polymer composites with high thermal conduction could be possible.…”
Section: Structure and Physico-chemical Properties Of Graphenementioning
confidence: 85%
“…2500 W · m − 1 · K − 1 ). [ 9 ] These results indicate that the crystallinity of the 2D sheets affects signifi cantly the thermal properties. Therefore, if one is to exploit the outstanding thermal properties of graphene, it is important to synthesize extremely high crystalline graphene so that the fabrication of heat dissipaters and polymer composites with high thermal conduction could be possible.…”
Section: Structure and Physico-chemical Properties Of Graphenementioning
confidence: 85%
“…Due to the scattering effect induced by GBs, the thermal conductivity of CVD-grown polycrystalline graphene is generally lower than that of exfoliated graphene [275]. In non-equilibrium MD simulations, Bagri et al [276] found a jump in temperature at tilt GBs when a constant heat flux was applied, and they calculated the boundary conductance by relating the jump in temperature to the heat flux.…”
Section: Disorders In Graphene Structurementioning
confidence: 99%
“…[52][53][54] It is well known that the properties of graphene may be strongly influenced by the supporting substrate; hence studies on free-standing graphene are of enormous interest. [55][56][57] The graphene TEM grid was electrochemically tested with two well-known redox couples;…”
Section: Wetting and Electrochemistry Of Supported And Suspended Grapmentioning
confidence: 99%